Terrestrial Mollusks of the Fergana Valley and Adjacent Mountainous Areas: Biological Diversity - Pardabayevna, Gaibnazarova Feruza; To`rabek o`g`li, Musabekov Ulug`bek (American Journal of Biology and Natural Sciences, 2026)
This article analyzes the biological diversity of terrestrial mollusks distributed in the Fergana Valley and adjacent mountainous regions based on a comprehensive approach. Within the framework of the study, the species composition, systematic structure, morphometric indicators, and ecological groups of mollusks found in the region were studied. According to the data obtained, 150–190 species of mollusks have been recorded in this area, among which the species of the family Enidae are dominant.